2022
DOI: 10.3390/su14042073
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Online Product Reviews and Muslim Fashion Innovation for Resilience during the New Normal in Indonesia

Abstract: The COVID-19 pandemic in Indonesia has harmed the fashion sector, particularly SMEs (small and medium-sized enterprises). In the wake of the epidemic, the Muslim Fashion Shop (MFS) sector has experienced a drop in sales. Therefore, developing innovative products and excellent customer approaches are critical to MFS resilience. This pandemic has additionally affected the shift from offline to online sales channels. Online sales features, referred to as online product reviews (OPRs), allow customers to leave com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
3
0
3
Order By: Relevance
“…With a focus on the textile industry, Appel and Hardaker (2021) found that aiming for a "bounce back" to a pre-crisis state and re-organising existing practices are amongst the resilience strategies. Nurcahyanie et al (2022) found that for Muslim fashion in Indonesia, features or customer requirements from online product reviews would enable designers to develop fashion products in the post-pandemic new normal. Similarly, Ali et al (2021) found a set of factors to improve resilience capability against vulnerability in readymade garments.…”
Section: Resilience Management Following the Covid-19 Pandemicmentioning
confidence: 99%
“…With a focus on the textile industry, Appel and Hardaker (2021) found that aiming for a "bounce back" to a pre-crisis state and re-organising existing practices are amongst the resilience strategies. Nurcahyanie et al (2022) found that for Muslim fashion in Indonesia, features or customer requirements from online product reviews would enable designers to develop fashion products in the post-pandemic new normal. Similarly, Ali et al (2021) found a set of factors to improve resilience capability against vulnerability in readymade garments.…”
Section: Resilience Management Following the Covid-19 Pandemicmentioning
confidence: 99%
“…En correspondencia con Nurcahhyanie et al (2022), en esta investigación se comprueba empíricamente desde el paradigma de la explotación y exploración de conocimientos y habilidades, que la innovación ejerce una influencia positiva y elevada sobre la resiliencia en los restaurantes del Valle de Toluca, presentando un fuerte poder y relevancia predictiva. Además, se encontró que la capacidad de afrontar está vinculada con la transmisión, la transformación y el aprovechamiento del conocimiento existente en las empresas (Atuahene-Gima, 2005).…”
Section: Discussionunclassified
“…La generalidad de los estudios ha puesto de manifiesto la relación entre las dos variables (Buliga et al, 2016;Fandiño et al, 2019;Nurcahhyanie et al, 2022). Igualmente, modelos de la influencia de la resiliencia sobre la innovación han sido utilizados (Do et al, 2022;Hallak et al, 2018).…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…When it comes to online reviews and purchasing in􀅫luences, the age factor has a signi􀅫icant impact on people's decisions. Nurcahyanie, Singgih, and Dewi (2021) investigated how older adults make purchasing decisions based on both product features and reviews. However, millennials prefer high-rated pro􀅫iles and brands when purchasing any product, irrespective of product features.…”
Section: Introductionmentioning
confidence: 99%